Current Female Firefighters’ Perceptions, Attitudes, and Experiences with Injury - Hollerbach, Brittany S. (Int Fire Serv J Leadersh Manag, 2017)
Research presented here examines how the demands of fire fighting uniquely affect women. A national sample of 73 female firefighters and fire-service leaders participated in focus groups and key informant interviews. Participants were asked about perceived threats to safety and standard operating procedures (SOPs) that lead to injury regarding gender differences. A thematic qualitative analysis was conducted and the following six themes were identified: (1) impact of working in a male-dominated field, (2) harassment, (3) similar rates/types of injury, (4) inadequate training, (5) ill-fitting gear, and (6) functional techniques/endurance. Both chronic and acute injuries/causes were discussed. Future direction will require diversity education and new training methodologies for the fire service.